MODALITY OF ENUNCIATION EXPRESSION - Padalka , Julia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is devoted to the study of the modality of enunciation expression. The article on the material of the Spanish language considers and analyzes sentences with the use of enunciations. Modality is an interlevel communicatively directed grammatical supercategory that indicates the relationship of sentence content to reality from the speaker’s point of view, has a complex, multifaceted expression, structured by three types of categories: morphological modality, syntactic modality and lexical and grammatical modality. The modality of expression manifests itself in two ways: on the one hand, it concerns the speaker, whose goal is self-representation, as well as the establishment of the social status of the addressee; on the other hand, it affects the interlocutor when it comes to receiving a certain reaction (positive or negative) to the message, when there is a need to encourage the communication partner to perform or not perform a certain action. Therefore, there is a process of subjective coding (sender) and decoding (addressee) of the propositional content of a statement. An utterance is an act of creating a message, a complex process of its creation or, in other words, an individual act of using language, in comparison with the utterance, the result of the utterance. Thus, in general, the analysis of the statement is to study the reflection of the subject in the message. __________ References: • Сadenaser, http://cadenaser.com/ser/2016/10/30/deportes/1477830622_174413.html • Cely, H. Semántica de los verbos que denotan preparación de alimentos en el español de Colombia (Tunja: Universidad Pedagógica y Tecnológica de Colombia, (Tesis de grado), 1981). • Gramática descriptiva de la lengua española (Madrid: Espasa, 1999): • Hermoso, A. Gonzáles, Cuenot, J. R., Alfaro, M. Sánchez. Curso práctico. Gramática de español lengua extranjera (Madrid: Edelsa, 1998), 272. • Palmer, F. R. Modality and the English Modals (N.Y.: Longman, 1990), 256. • Palmer, F. R. Mood and Modality, 2nd ed. (Cambridge: Cambridge University Press, 2001), 236.